Utilização da simulação molecular na predição da acumulação de alcanos em estruturas metalorgânicas - Mileo, Paulo Graziane Mendonça (2014)
Natural gas, which consists mostly of methane, is a fuel that has been expanding in the global energy market by having a cleaner burning than other petroleum derivatives and are more energy efficient. However, it has a great disadvantage compared to other fuels: it is difficult to be stored due to its low energy density. Microporous materials have been used to increase the energy density by adsorption. However, one of the problems encountered in using these materials it comes to the decrease in adsorption capacity after charge and discharge cycles of the storage tanks. The study of this problem, however, requires a large number of experiments and a relatively sophisticated equipment. This paper proposes themolecular simulation as a valid methodology to study the retention of alkanes in activated carbon, and eight metalorganic structures: IRMOF - 1, ZIF - 8, CuBTC, PCN- 11, PCN -14, UiO -66, MIL -100 and MIL- 101. We considered the natural gas as a mixture of methane (C1), ethane (C2), propane (C3) and butane (C4) in the proportions respectively 84,7:10:0,9:0,1. For the validation of the models used in the simulations, the simulated isotherms of C1, C2, C3 and C4 were adjusted to fit the experimental ones, obtained from the literature data for every material. Multicomponent isotherms were then performed, the retention of hydrocarbons were studied as well as the influence of compositional and structural factors to this phenomenon. We noticed that the MOFs MIL-100 and ZIF-8 are the most recommended to use in GNA tanks according to the criteria of capacity, adsorption efficiency and stability. We verified as well that MOFs that have adsorption sites too localized present a larger tendency to the accumulation of hydrocarbons.